Educational Governance: A Literature Review - Idris Onia, Saifaldin (Journal of Governance and Administrative Reform, 2025)
Abstract Educational governance encompasses the institutional structures and operational dynamics through which educational systems assign responsibilities, formulate objectives and strategies, and implement policies and programs. This study aims to conceptualize governance with a specific focus on its application in the educational context. Employing a qualitative and interpretive research approach, the study draws on a comprehensive review of existing literature, particularly scholarly works on educational governance. The paper examines the foundational definitions and theoretical underpinnings of governance and educational governance. The findings suggest that governance within educational institutions constitutes the rational and lawful exercise of administrative authority and decision-making, governed by legal frameworks, standards, and rules that define the relationship between institutional leadership and stakeholders. The study concludes by recommending the integration of educational governance as a core component in the training programs for school directors, emphasizing its role in fostering institutional development and promoting good governance practices within schools. Keywords: governance; educational governance; good governance; literature review   Abstrak Tata kelola pendidikan mencakup struktur kelembagaan dan dinamika operasional yang memungkinkan sistem pendidikan untuk mendistribusikan tanggung jawab, merumuskan tujuan dan strategi, serta melaksanakan kebijakan dan program. Studi ini bertujuan untuk mengonseptualisasikan tata kelola, dengan fokus khusus pada penerapannya dalam konteks pendidikan. Dengan menggunakan pendekatan penelitian kualitatif dan interpretatif, kajian ini mengacu pada tinjauan literatur yang komprehensif, terutama terhadap karya-karya ilmiah mengenai tata kelola pendidikan. Artikel ini mengkaji definisi dasar serta landasan teoretis dari konsep tata kelola dan tata kelola pendidikan. Temuan menunjukkan bahwa tata kelola dalam lembaga pendidikan merupakan bentuk pelaksanaan kewenangan administratif dan pengambilan keputusan yang rasional dan sesuai hukum, yang diatur oleh kerangka hukum, standar, dan aturan yang menetapkan hubungan antara kepemimpinan institusi dan para pemangku kepentingan. Studi ini menyimpulkan dengan merekomendasikan integrasi tata kelola pendidikan sebagai komponen utama dalam program pelatihan bagi para kepala sekolah, dengan penekanan pada perannya dalam mendorong pengembangan institusional dan penerapan praktik tata kelola yang baik di lingkungan sekolah. Kata kunci: tata kelola; tata kelola pendidikan; tata kelola yang baik; tinjauan literatur